Social contexts of traumatization and healing - Ajduković, Dean (Array, 2003)
After massive organized violence such as war, the consequences are multiple and they surpass individual suffering, traumatization and losses. Such man-made massive traumatization, followed by losses and prolonged uprooting and ethnic cleansing leave behind the people whose basic belief that the world is a fairly just and predictable world has been shattered. Once the hostilities are done with, the rebuilding can begin. This should also include the process of social reconstruction during which the people in local communities are expected to reconnect, to acknowledge the fact that former adversaries will have to live in the same community, they need to start rebuilding trust and everyday communication. In other words, this process is about normalizing the everyday life in a community. However, there are a number of barriers to such processes that are more obvious, while resources that can facilitate it are often hidden. Among these barriers most notable are unfulfilled existential needs, feelings of fragmentation of social life, deep feelings of distrust, complicated grieving, consequences of trauma and perception of being betrayed by the people one has trusted. The barriers to social reconstruction were illustrated using the data from a multi-methodological multi-year study in the city of Vukovar that has become notorious for the suffering of inhabitants and the atrocities. Creative models of interventions that facilitate community strengthening, help the process of social reconstruction, decrease tensions among the groups in conflict, and provide assistance to the most affected and traumatized individuals are needed. In fact, they contribute to the progression to stability of communities, peace and eventually to reconciliation. If empowerment of a destabilized community is a tool, it is essential for the people to integrate their painful collective experiences so that they could turn towards the future. This is also the only way to break the circle of violence and victimization. The model describing factors and possible relations that affect social reconstruction of a destabilized community will be presented. The pyramid model of community psychosocial interventions based on the public mental health approach was also described.